PEMBUATAN PROTOTIPE ALAT UKUR KESUBURAN TANAH BERBASIS ARDUINO UNO - Hamzah Afandi; Muchamad Eris Rizqul Ulum (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Soil fertility is a necessity to support a crop’s life, and it affects crop’s growth as well. Based on that, this research to create a prototype to measure soil fertility is conducted. This prototype needs some main components such as an Arduino UNO, iron rod, iron sheeting, a non-inverting op-amp circuit, LCD 16x2 IIC, and a 5V power supply. Arduino UNO acts as a main control on the prototype. The soil fertility sensor is an iron rod and iron sheeting placed parallel to each other. The sensor acts as soil fertility level reader. LCD 16x2 IIC and an LED as an output. Sensor will measure the soil’s fertility and send the information (in voltage) to the non-inverting op-amp circuit to be amplified. The result of this research indicates that sensor can measure soil fertility. Non-inverting op-amp circuit can amplify the received signal and forward the signal to Arduino UNO, which then will be processed and become an LCD and LED output. Voltage measurement result of the humus soil is 643mV and amplified to 1294mV as an ideal soil for crops to be planted. With this prototype, soil fertility can be measured. Keywords Arduino Uno, LED, LCD I2C, OP-AMP CA3140, Kesuburan Tanah